2021
DOI: 10.3390/ijerph182413405
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Demographic, Socio-Economic and Geographic Factors on Mortality Risk among People Living with Dementia in England (2002–2016)

Abstract: Increasing numbers of people living with dementia (PLWD), and a pressured health and social care system, will exacerbate inequalities in mortality for PLWD. There is a dearth of research examining multiple factors in mortality risk among PLWD, including application of large administrative datasets to investigate these issues. This study explored variation mortality risk variation among people diagnosed with dementia between 2002–2016, based on: age, sex, ethnicity, deprivation, geography and general practice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…However, our findings emphasise less need for acute healthcare among PLWD from ethnic minority backgrounds. There is lower mortality risk among PLWD from ethnic minority backgrounds (Watson et al, 2021 ), a finding which may be consistent with younger demographics (insufficiently controlled for in our analysis) and reduced severity of dementia (Parveen & Oyebode, 2018 ). Existing research highlights the barriers in accessing quality healthcare for PLWD from ethnic minority backgrounds (Cooper et al, 2010 ; Lin et al, 2020 ; Mukadam et al, 2011 ; Pham et al, 2018 ), but with reduced severity, there is also less frequent contact with healthcare services (Duran-Kirac et al, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, our findings emphasise less need for acute healthcare among PLWD from ethnic minority backgrounds. There is lower mortality risk among PLWD from ethnic minority backgrounds (Watson et al, 2021 ), a finding which may be consistent with younger demographics (insufficiently controlled for in our analysis) and reduced severity of dementia (Parveen & Oyebode, 2018 ). Existing research highlights the barriers in accessing quality healthcare for PLWD from ethnic minority backgrounds (Cooper et al, 2010 ; Lin et al, 2020 ; Mukadam et al, 2011 ; Pham et al, 2018 ), but with reduced severity, there is also less frequent contact with healthcare services (Duran-Kirac et al, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
“…2015 Indices of Multiple Deprivation (IMD) quintile and GP urban/rural classification was available via data linkage using patients’ GP ID. This study includes these explanatory factors for healthcare use among PLWD, as research illustrates differential provision and quality of healthcare, and health outcomes for PLWD by age (continuous), sex, ethnicity and deprivation, and by spatial factors including level of urbanity/rurality (Rahman et al, 2020 ; Watson et al, 2020 , 2021 ; Wu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While males and females had similar survival duration and neurofilament levels, the authors suggested that since females live longer than males in general, that absence of differences in survival could indirectly mean that females have a more aggressive form of disease. Electronic health records from general practices across the United Kingdom were used to investigate various risk factors for mortality in dementia [27 ▪▪ ]. These factors included mixed/other ethnicity (hazard ratio [HR] 1.18), lower socioeconomic status/more deprived areas (HR 1.18) and living in the South Central region of the UK (HR 1.39) and being male (HR 1.24).…”
Section: Epidemiological and Clinical Studiesmentioning
confidence: 99%